A pedagogical case on active learning regarding to Kirchhoff's circuit laws. Issue 2 (April 2019) - Kang, Rui; Lin, Yixuan; Wang, Yuexin; Wu, Hao; Wu, Minghe; Teng, Baohua
Kirchhoff's circuit laws are important basic concepts in many basic disciplines, such as electricity and circuitry. However, in the usual teaching process, teachers often teach this knowledge using some simple examples of analysis and calculation but without deep discussions. As a result, students could not have a deep understanding about these concepts or not apply the concepts on actual problems flexibly. Therefore, passive learning habits are formed. The lack of self-exploration awareness and comprehensive ability would result in a poor learning effect. This paper designs a specific application scene of Kirchhoff's circuit laws using a multi-channel resistor network. With this application, students can construct the knowledge system autonomously, find the problems proactively, solve the problems timely, and combine the research-based autonomous learning with extracurricular open mutual learning; so, their active learning ability will be promoted to a large extent. Compared with the past teaching methods, this pedagogical case highlights the following advantages of active learning. Firstly, it highlights the process of guiding students to study the object from a small-scale resistor network to a complex and large-scale multi-channel resistor network. Secondly, it embodies the concrete application of calculus knowledge in various basic courses with the help of perfect mathematical deduction. Thirdly, it exercises students' programming ability by using MATLAB to numerically simulate theoretical results. Finally, this case practices students' hands-on experimental ability by constructing real resistor circuits and verifying the theory and simulation results. In addition, we get good feedback from students on the teaching effect through the questionnaire survey.